NUMERICAL ANALYSIS OF THIN BEAMS RESTING ON NONLINEAR ELASTIC FOUNDATIONS (Journal of Engineering, 2010)
The finite difference method is used for solving the basic differential equation for the elastic deformation of a thin beam supported on a nonlinear elastic foundation. A tangent approach is used to determine the modulus of subgrade reaction after constructing a second degree equation for load-deflection diagram. Results of plate loading test of soil obtained in Iraq were used in the analysis. An iterative approach is used for solving the nonlinear problem until the convergence of the solution. The method of analysis, as programmed for a computer solution, considers the continuous elastic, nonlinear foundation to be active only when the beam is pressing against the foundation. Two examples of with simply supported beams are presented to illustrate the application of the method of analysis.